1963
DOI: 10.1111/j.1476-5381.1963.tb01475.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Initial Adrenergic Effects of Bretylium and Guanethidine

Abstract: Treatment with phenoxybenzamine and dichloroisoprenaline prevented the rise of blood pressure, contraction of the nictitating membrane and increase in cardiac contractile force produced by intravenous injections of bretylium and guanethidine in anaesthetized or spinal cats. Treatment with cocaine, imipramine or reserpine reduced the sensitivity to bretylium and guanethidine of the spinal cat. In the spinal cat treated with reserpine, sensitivity to the drugs could be restored by an infusion of noradrenaline. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1965
1965
1991
1991

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…The pressor phase was generally preceded by a transient fall in blood pressure, a phenomenon which has been reported for both bretylium and guanethidine sulphate (Gokhale, Gulati & Kelkar, 1963). A contraction of the nictitating membrane occurred simultaneously with the rise in blood pressure and was sustained for the remainder of the experiment.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The pressor phase was generally preceded by a transient fall in blood pressure, a phenomenon which has been reported for both bretylium and guanethidine sulphate (Gokhale, Gulati & Kelkar, 1963). A contraction of the nictitating membrane occurred simultaneously with the rise in blood pressure and was sustained for the remainder of the experiment.…”
Section: Resultssupporting
confidence: 57%
“…Effect on the bloodpressure, heart and nictitating membranes of the anaesthetized or spinal cat SK&F 70418 (5 or 10 mg/kg, intravenously) caused an initial prolonged rise in blood pressure, followed by a fall to or below the control level within 5 hr. The pressor phase was generally preceded by a transient fall in blood pressure, a phenomenon which has been reported for both bretylium and guanethidine sulphate (Gokhale, Gulati & Kelkar, 1963). A contraction of the nictitating membrane occurred simultaneously with the rise in blood pressure and was sustained for the remainder of the experiment.…”
Section: Effect On the Nictitating Membrane Of The Conscious Catsupporting
confidence: 57%
“…Sympathomimetic agents, such as dextroamphetamine, which depend on stored catecholamines for their action, might also be expected to act at these catecholamine storage sites and then to compete with and perhaps to displace the blocking drugs. The facts that guanethidine produces adrenergic effects indirectly through a release of amines from their storage sites I , 2, G, 8 and that many indirectly acting sympathomimetic amines have an adrenergic neuron blocking action 5 also support the idea of a common site of action for these two drugs. Reduction in the cold-pressor response in control, hypertensive patients following methylphenidate, observed in the present study, also suggests a guanethidine-like adrenergic neuron blocking action for these substances.…”
Section: Discussionmentioning
confidence: 90%
“…Gokhale, Gulati & Kelkar (1963) have shown that the initial pressor response of the cat to guanethidine is unaltered by adrenalectomy and have concluded that the adrenal medulla is not a major site of catecholamine released by guanethidine. The present studies also show that guanethidine possesses very limited ability as a medullary secretogogue, and thus it appears that the adrenal medulla does not contribute significantly to the quantity of catecholamine released by guanethidine.…”
Section: Drugs Usedmentioning
confidence: 99%